Import Components and Import Multipliers in Indonesian Economy: World Input-Output Analysis - Muchdie Muchdie; M Handry Imansyah; M Kusmawan; Hamid Al-Jurfri (Universitas Negeri Malang, 2018)
This paper calculates, presents and discusses on import components and the impact of final demand change on Indonesian imports using Indonesian 36 sector input-output tables of years: 2000, 2005, 2010 and 2014 from World Input-Output Tables. The results showed that firstly, Indonesian import components of input were, on average, more than 20 percent; meaning that input that locally provided were less than 80 percent. Secondly, Indonesian import of input had increased significantly from US 36,011 million in 2000 to US 151,505 million in 2014. Thirdly, Indonesian imports have been dominated by Sector-3: Manufacture of food products, beverages and tobacco products, Sector-4: Manufacture of textiles, wearing apparel and leather products, Sector-24: Construction, Sector-25: Wholesale and retail trade and repair, and Sector-26: Transportation and post services. Fourthly, by country of origin, Indonesian imports have been dominated by Japan, Korea, the USA, Australia, and China. Imports from Australia, Japan, and the US have been decreased significantly, but import from China has steadily increased. Finally, highest sectoral import multipliers occurred if final demands change in Sector-1: Crop and animal production, forestry, fishing and aquaculture, Sector-2: Mining and quarrying, Sector-23: Water collection; sewerage; waste collection, treatment and disposal activities, and Sector-30: Real estate activities, but there was no significant difference of import multipliers for country origin of import.Keywords: import components, sectoral import multiplier, spatial import multiplier.JEL Classification: C67, D57, F17